Smart remote sensing weather station - Numan, Abdullah- Al-; Islam, Md. Imranul; Hossain, Md. Amzad; Hasan, Md. Rakibul (BRAC University, 2014)
This thesis report submitted in partial fulfillment of the requirement for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2014.